KUALITAS PELAYANAN, PROMOSI PENJUALAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA PENGGUNA TRANSPORTASI ONLINE GRAB BIKE DI KOTA SURAKARTA - Dewi Darma Wati; Bambang Mursito; Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to examine the effect of service quality, sales promotion and price perception on customer satisfaction. The population used in this study is not limited to the grab application users in Surakata City. The sample used in this study was 100 people determined using the Sugiyono formula. The sampling technique used is the non probability sampling method with the sampling method used is accidental sampling and analyzed using multiple linear regression with SPSS version 21. The results of this study can be seen that the calculated F value of 32.274 (p> 3.09) and a significance value of 0.000 (p 1.98) and the significance value was 0.001 (p 1.98) and the significance value was 0.047 (p 1.98) and the significance value was 0.015 (p